Pengembangan Bahan Ajar Suplemen Pembelajaran Sub-sub Materi Tipe-Tipe Gunung Berapi Untuk Siswa Kelas VII Sekolah Menengah Pertama - Permadi, M.Sigit; -, Drs.Muhammad Musiyam M.T.P (2017)
Three purposes of the study are to : (1) know performance of supplement teaching material for learning of volcano types sub sub themes for class VII of secondary school; (2) develop a supplement teaching material for learning of volcano types sub sub theme for class VII; (3) know improvement of learning achievement using the supplement teaching material for learning of volcano types sub sub theme with the NHT (Numbered Head Together) strategy for class VII. The study is a research of development one by using Dick and Carey model. The study was conducted in SMP Negeri 1 Kemalang for a class VIIA totalling 31 students with experimental design One group pretest-posttes design and uses strategy NHT (Numbered Head Together) to look at improving students learning outcomes using supplement teaching material. The sampling using simple random sampling. Data was obtained by using obseravation, questionnaire, test and documentation. The study resulted in a product of supplement teaching material for learning of volcano types sub sub theme for class VII meeting with the needs of students and teachers. This supplement teaching material was validated by experts and tried out with teacher and students. Experiment results using the test a paired sample T test by result tabulating the pretest 42% and increase after posttest 71%. The result show supplement teaching material developed with NHT (Numbered Head Together) strategy effective researchers to use in learning.